PREVENTION OF SEXUAL VIOLENCE THROUGH PUBERTY EDUCATION AT SDIT MUTIARA INSAN BEKASI REGENCY - Erry Utomo; Nurfadhilah; Dewi Purnamawati; Dewi Andayani (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Compared to a few decades ago, puberty now happens earlier, and the frequency of sexual assault is rising wildly. The purpose of this study is to examine how puberty education affects high-grade elementary school students' awareness of sexual assault prevention. With a facilitator in each class, the research design employs a quasi-experimental format of concurrent lectures and conversations lasting 60 minutes. 22 fourth-graders, 31 fifth-graders, and 31 sixth-graders make up the participants. Ten true-false questions from a pre-and post-test were used to gauge knowledge. The T-test was utilized in data analysis. The understanding of high school students significantly increased (P value 0.0001). All class discussions showed an exceptionally lively exchange of thoughts, and several students were particularly aggressive and engaged in raising issues of psychological (the recognition and control of emotions) and social (interpersonal connections and communication) interest. Continuous education is important, along with teaching strategies that are not the same as pedagogy or andragogy but rather suitable for the typical characteristics of adolescents.